Phosphoinositide Signaling and Mechanotransduction in Cardiovascular Biology and Disease - Krajnik, Amanda; Brazzo, Joseph A.; Vaidyanathan, Kalyanaraman; Das, Tuhin; Redondo-Muñoz, Javier; Bae, Yongho (Frontiers in Cell and Developmental Biology, 2020)
Phosphoinositides, membrane-bound phospholipids, are critical signaling molecules at the interface among the extracellular matrix, cell membrane, and cytoskeleton. Phosphoinositides are essential regulators of many biological and cellular processes, including but not limited to cell migration, proliferation, apoptosis, and differentiation, as well as cytoskeletal rearrangement and actin dynamics. Over the years, a multitude of studies have uniquely implicated phosphoinositide signaling to be crucial in cardiovascular biology and a dominate force in the development of cardiovascular disease and its progression. Independently, cellular transduction of mechanical forces, or mechanotransduction, in cardiovascular cells is widely accepted to be critical to their homeostasis and can drive aberrant cellular phenotypes and resultant cardiovascular disease. Given the versatility and diversity of phosphoinositide signaling in the cardiovascular system in addition to the dominant regulation of cardiovascular cell function by mechanotransduction, the molecular mechanistic overlap and extent to which these two major signaling modalities converge in the cardiovascular cell remain unclear. In this review, we discuss and synthesize recent findings that rightfully connect phosphoinositide signaling to cellular mechanotransduction in the context of cardiovascular biology and disease, in which we specifically focus on phosphatidylinositol-4,5-phosphate, phosphatidylinositol-3,4,5-phosphate, phosphatidylinositol 3-kinase, and phosphatidylinositol-4-phosphate 5-kinase. Throughout the review, we discuss how specific phosphoinositide subspecies have been shown to mediate biomechanically-sensitive cytoskeletal remodeling in cardiovascular cells. Additionally, we discuss the direct interaction of phosphoinositides with mechanically-sensitive membrane-bound ion channels in response to mechanical stimuli. Furthermore, we explore the role of phosphoinositide subspecies in association with critical downstream effectors of mechanical signaling in cardiovascular biology and disease.